Current knowledge and “myths” about celiac disease among physicians in the Republic of Kazakhstan: A countrywide cross-sectional study - Kozhakhmetova, Aizhan; Aidossov, Serzhan; Kapassova, Aissulu; Borsoldayeva, Karlygash (Frontiers in Public Health, 2022)
Background Celiac disease (CD) is a common genetically predisposed autoimmune condition affecting the gut and other organs. Disease awareness is one of the key components of early case identification. This study aimed to assess awareness about CD among primary care physicians, who are the front-liners in suspecting the diagnosis, and other medical specialists. Methods and findings The questionnaire for this survey-based study was created based on the latest international guidelines on CD and included a consent form, 5 general questions (age, gender, etc.), and 10 specific questions concerning CD. Overall, 232 respondents from 13 country provinces (out of 14) and two republican cities were recruited for this study. Of them, 110 (47.4%) were primary care physicians and 122 (52.6%) other medical specialists, including 10 (4.3%) gastroenterologists. A scoring system was used to classify the level of awareness of participants into 3 categories, namely, poor, fair, and good. Analysis of responses revealed poor awareness in 59.4% of physicians, associated with work in republican/province/district/rural/village hospitals (p = 0.004), male gender (p = 0.006), and age of 40–50 years (p = 0.02). The most common “myths” about CD were the following: “symptoms are always obvious in children” or “in adults” (92.5 or 88.4% of respondents, respectively); “genetic mutation HLA DQ2/DQ8 causes the development of CD in all carriers of the mutation” (51.3%); “CD is a disease of children only” (12.5%); and “is triggered by dairy products” (8.6%). Genotyping of HLA DQ genes has been recommended in case of CD suspicion by every third respondent and was advocated as a “golden standard” confirmatory test by every fifth respondent. A quarter of respondents revealed their incorrect treatment strategies: gluten-free diet for 1 month, dairy-free diet, Helicobacter pylori eradication therapy, or responded that did not know how to treat. Overall, 93.5% of respondents expressed intention to learn more about CD, while the rest 6.5% thought that they knew enough, although their knowledge was poor. Conclusion This study revealed a poor level of awareness among physicians in Kazakhstan and identified common misconceptions about CD, which potentially could lead to incorrect application of diagnostic tests, delay in diagnosis, and inefficient treatment. Development and implementation of educational programs as well as promotion of self-learning would increase awareness and unravel misconceptions.